Adsorption and photocatalytic performance of bentonite-titanium dioxide composites for methylene blue and rhodamine B decoloration. Issue 12 (December 2017) - Laysandra, Livy; Sari, Meri Winda Masnona Kartika; Soetaredjo, Felycia Edi; Foe, Kuncoro; Putro, Jindrayani Nyoo; Kurniawan, Alfin; Ju, Yi-Hsu; Ismadji, Suryadi
Abstract: Bentonite − TiO2 composites were prepared by impregnation of TiO2 and bentonite, followed by microwave irradiation processes. The composites were characterized using FTIR, SEM, XRD, and nitrogen sorption methods. Anatase phase of TiO2 in all composites are observed through XRD diffraction peaks and surface morphology of the composites. The adsorption and photocatalytic capabilities of the composites were tested in liquid phase adsorption of methylene blue and Rhodamine B. The adsorption and photocatalytic degradation experiments were conducted in the presence or absence of UV light irradiation. Langmuir and Freundlich models were employed to correlate the experimental adsorption data, and it was found that Langmuir gave better performance in correlating the experimental data. Modification of Langmuir equation to accommodate photocatalytic degradation process was conducted, and the model could represent the experimental results very well.